KUALITAS KETERWAKILAN RAKYAT MELALUI DEWAN PERWAKILAN RAKYAT MENURUT SISTEM POLITIK DI INDONESIA - Hasmin, Mohammad Yusuf (Fakultas Hukum, Universitas Muslim Indonesia, 2017)
Representation of the people through the Parliament is not yet fully qualified, due to the influence of the party's board members is more dominant than the existence as the people's representatives who are directly elected by the people. Political system adopted can not fully realize the representation of the people who correspond the expectations of society, although it has been supported by a system of democratic elections based on the sovereignty of the people. Abstrak Representasi rakyat melalui DPR belum sepenuhnya memenuhi syarat, karena pengaruh anggota dewan partai lebih dominan daripada keberadaannya sebagai wakil rakyat yang dipilih langsung oleh rakyat. Sistem politik yang diadopsi tidak dapat sepenuhnya mewujudkan representasi rakyat yang sesuai dengan harapan masyarakat, walaupun telah didukung oleh sistem pemilihan demokratis berdasarkan kedaulatan rakyat.